Pendekatan untuk Meningkatkan Keterampilan Menulis Kreatif Siswa: Sebuah Scoping Review - Ferdiyanto, Fahmy; Muhid, Abdul (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
Writing is an important skill for expressing ideas and feelings; however, without proper guidance, many students struggle to develop it. The objective of this research is to identify various effective approaches to developing students' creative writing skills. This study employs a scoping review method with a systematic approach that includes topic design, searching, selection, grouping, drafting, summarizing, and writing study results. Article searches were conducted through Google Scholar and ERIC using the PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis) method. The articles reviewed were published between 2019-2025, with 15 selected articles for further discussion. The results of the scoping review indicate that creative writing skills can be developed through various approaches. This research concludes that the development of students' creative writing skills can be achieved through diverse methods, including story-based methods, learning models focused on local wisdom and multiliteracies, as well as the use of digital media and structured instruction. The selection of appropriate methods, considering media, models, and students' abilities, is crucial for the successful development of creative writing skills. Further research is needed to explore the effectiveness of these approaches on various participants in the context of education.